90.6k views
1 vote
Solve ax + by = c, for b

User Thedz
by
5.1k points

2 Answers

1 vote

Answer:


b= (c-ax)/(y)

Explanation:

We can solve the question by isolating the variable

Step 1: Subtract ax from both sides.


ax+by=c\\\\ax+by-ax=c-ax\\\\by=-ax+c

Step 2: Divide both sides by y.


(by)/(y) = (-ax+c)/(y)\\\\\\b= (-ax+c)/(y)

The answer is:


b= (c-ax)/(y)

User Jinett
by
4.9k points
7 votes

Answer:

b=c-ax/y

Explanation:

1) ax + by = c

-ax

2) by = c - ax

3) by/y = b and c - ax/y

4) b = c-ax/y

User Galusben
by
5.8k points